Predicting Early Awakening from Coma after Intracerebral Hemorrhage - Goodman, Diana; Kasner, Scott E.; Park, Soojin (Frontiers in Neurology, 2013)
Introduction – Given the high morbidity and mortality associated with intracerebral hemorrhage (ICH), family members and healthcare providers base early supportive management decisions, at least in part, on expected prognosis. In the comatose patient with ICH, this short-term prognosis is most overtly characterized by regaining of consciousness. Methods – A retrospective consecutive cohort of 51 patients admitted to a neuroICU with ICH and admission Glasgow Coma Scale score ≤ 8 was identified. Logistic regression was performed to assess the association of baseline characteristics and treatment parameters associated with awakening. Results – Awakening from coma was observed in 53% of ICH patients: 83% with an initial GCS score of 7-8, 43% with an initial score of 5-6, and 20% with an initial score of 3-4. Awakening from coma in the cohort of 27 patients who regained consciousness occurred in 59% of patients by day 2, 89% by day 7, and 96% by day 9. In multivariable analysis, only higher admission GCS score was associated with a greater likelihood of awakening from coma (OR 4.9 [95%CI 1.9–13] per 2-point category, p=0.001). DNR status during the first 24 hours was not associated with awakening but was at later time points. Conclusion – GCS score is the predominant initial predictor of early awakening in patients who present in coma after ICH. Patients who regained consciousness typically did so within the first 9 days of hospital admission.